Causal role of endothelial dysfunction in ischemic stroke and its subtypes: A two-stage analysis - Qian Wu; Jiabo Cui; Yao Jiang; Xiaoxin Li; Chongge You (SLAS Technology, 2025)
Objective: Endothelial dysfunction is implicated in the pathogenesis of ischemic stroke (IS), but its causal role remains unclear. This study systematically investigates the causal relationship between endothelial dysfunction proteins and IS and its subtypes through integrated observational and genetic evidence. Methods: A two-stage study was conducted combining systematic meta-analysis and Mendelian randomization (MR). The meta-analysis integrated data from 29 observational studies to assess associations between endothelial dysfunction proteins (vWF, sE-selectin, sP-selectin, ICAM-1, VCAM-1, sLOX-1, VEGF, ET-1, SDF-1) and IS. This meta-analysis was registered online (PROSPERO ID: CRD42023461783). Subsequent MR was applied to discern the causal effects of the endothelial dysfunction proteins on IS and its subtypes, utilizing genetically instrumental variants. Results: A meta-analysis demonstrated significant correlations with IS for vWF, sE-selectin, ICAM-1, sP-selectin, sLOX-1, and VEGF (all p < 0.05). Furthermore, MR analysis showed that genetically elevated vWF increased the risk for any IS and cardioembolic stroke (CES), while E-selectin was causally linked to large-artery atherosclerosis stroke (LAS). Conclusion: This work offers causal evidence that endothelial dysfunction significantly contributes to IS, highlighting the thrombotic activity of vWF in CES and the inflammatory function of E-selectin in LAS. These findings not only offer valuable insights into the mechanisms underlying IS and its subtypes but also help inform personalized stroke prevention strategies.